Bedload Estimation: Case of Wadi El-Hammam in the North-West of Algeria - GLIZ, Mohamed; REMINI, Boualem (GeoScience Engineering, 2022)
In Algeria, only the transport of suspended sediment is measured, the rate of bedload in the global transport of solids is estimated, approximately. Measures of bed load transport in the field are very costly, due to flow disturbances. As a result, evaluations of this type of sediment transport are difficult to carry out in the absence of databases. In this article, we tried to quantify this mode of transport at the wadi El-Hammam using the formula of Meyer-Peter and Müller. Formula that seems best adapted to the physical characteristics and flow conditions of the wadi studied. The results obtained show that the calculated bedload ratio is between 0.6 and 28 % of the suspension. The quantities transported annually are very large and irregular as they vary from 2.3 to 32 Mg.km-2.year-1, characterising the Mediterranean mountains and semi-arid environments. A good correlation was found between the daily bedload flow and the liquid flow, the obtained model Qs = aQb, can be easily used to estimate the bedload transport at the Hacine hydrometric station, located at the output and without data concerning this phenomenon. Keywords: Bed load transport; Fergoug; Meyer–Peter and Müller formula; Suspension; Wadi El-Hammam.